Organizing in Administration and Management of Early Childhood Education (PAUD) - Fatihatun Jannah; Firyal Najla Waffiya; Mutiara Putri Amelia; Millah Hanifah; Suhardi Suhardi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Management in Early Childhood Education (PAUD) is an important aspect in creating a structured, effective, and efficient educational system. One of the main functions in management is organizing, which is the process of arranging, directing, coordinating, and controlling resources such as human resources, funds, facilities, and infrastructure in order to achieve organizational goals. In PAUD institutions, organizing is highly necessary so that the distribution of duties and responsibilities among divisions can run clearly and optimally. A well-designed organizational structure involves several elements, including the Foundation, Principal, Administration, Student Affairs, Curriculum, Public Relations, Facilities and Infrastructure, and students. Each section has roles and duties that support one another, such as the Foundation being responsible for funding and supervision, the principal acting as the operational leader, and other staff carrying out tasks according to their respective fields. This organizing process is also based on important principles, such as division of work, departmentalization, and delegation of authority. With these principles, the organization can operate harmoniously and avoid conflicts of duties or responsibilities. A clear organizational structure enables better coordination, increased work efficiency, and more directed achievement of educational goals. Therefore, organizing in PAUD management not only functions in the distribution of work but also creates a conducive learning environment for the comprehensive and sustainable development of early childhood.